静岡市立芹沢銈介美術館所蔵の魚皮衣について - 梶原, 洋; カジワラ, ヒロシ; Kajiwara, Hiroshi (東北福祉大学, 2014)
魚皮は、かつてユーラシア大陸全域の諸民族にとって生活に欠かせない材料であった。静岡市立芹沢銈介美術館所蔵の本魚皮衣はこれまですでに芹沢長介先生により紹介されているが、本論考では、主にアメリカ自然史博物館のラウファー資料との比較を元に、新たに背面文様の分類し解釈加えた。その結果、全体の文様構造は男女を表す吉祥文を図案化した晴着であること、はじめは魚皮の穴を塞ぐための単純な文様展開であったものが次第に複雑化したことなどを明らかにした。さらにこれまで注目されてこなかった左右対称に配置される「朱彩点状文」の存在を見出し、渦巻文だけに限られない文様構造も明らかにすることができた。本資料は、世界的な水準から見ても最も優れた魚皮衣の一つであることが確認できた The fish skin garment at the Serizawa Keisuke Art Museum in Shizuoka, Japan (Plate1) was acquired by late Professor Chosuke Serizawa around 1953. The garment was likely first discovered and purchased at a Nivkh village in Sakhalin (Karafuto in Japanese) by Professor Shuzo Ishida in 1914 during his expeditions there. Tanned fish skins (mostly Salmonidae) were light,water-resistant materials widely exploited for daily use among natives in Eurasia (fig. 2, 4, 5). Especially the nanai(previouslycalled"Gold") living along the Amur and its tributaries were famed for their excellent fish skin garments with skilful embroideryand splendid back appliques, and were known as the "fish skin Tartars" in China (fig.1). As a native folk art, fish skin garments were first described in detail by Berthold Laufer, a member of the Jesup North Pacific Expedition of the American Museum of Natural History led by the famous anthropologist F. Boas. Laufer's ethnographic monograph of 1902, "The Decorative Art of the Amur Tribe," provided excellent illustrations and explanations of fish skin garments in these regions. Comparing the garment from the Serizawa collection with those of Laufer (1902), Ivanov (1963), Okladnikov (1964, 1981), Smolyak (1984), Kocheshkov (1995), and so on, I have tried to ascertain the historical, ethnological and artistic significance of the Serizawa garment among the indigenous cultures of the Amur, Sakhalin and Hokkaido, and have made these principal observations: 1. The general style of the garment is very similar to those worn by noble women of the Qing dynasty in China (fig. 10). Fish skin garments were produced as wedding costumes presented to daughters by their mothers. The bell-like ...